PENGUATAN PENDIDIKAN KARAKTER DI SEKOLAH MELALUI PERAN GURU SEBAGAI FASILITATOR SISWA UNTUK MENINGKATKAN KOMPETENSI SIKAP SISWA - Pratiwi, Ika Indah; Suryati, Indah; Cahyo, Aji Nur; Setiaputra, Felix Indra (Fakultas Keguruan dan Ilmu Pendidikan, 2020)
Character education is the main program that must be in school. This study aims to evaluate evaluatively the strategy and implementation of character education by the teacher as a facilitator in improving the competence of students' attitudes at SMP Muhammadiyah 4 Sambi, Boyolali. In this study using qualitative research methods through descriptive explanations that use interviews, documentation, and direct observation related to the teacher's efforts when doing classroom learning and strengthening character education through school programs and in their responsibilities as educators. Research at SMP Muhammadiyah 4 Sambi, Boyolali shows that teachers have an important role in educating students, especially regarding character education because the character of students is an important part of educational outcomes, because education is not only about grades and academic results, but what is more important is character. which is in students to apply their knowledge in everyday life so that students can have good quality academics and be applied in all areas of community life and become good citizens.